Towards Circular Economy through Waste to Biomass Energy in Madagascar. (8th June 2021) - Qin, Ling; Wang, Mengjun; Zhu, Jinfu; Wei, Yuhu; Zhou, Xintao; He, Zheng
Abstract : Biomass energy, contributing to about 80% of the total energy supply, is considered an important energy source in Madagascar. Although around 80% of energy use comes from biomass energy, the current application method of biomass in Madagascar is still in the earliest stage, which is not safe and sustainable. This is because the main form of biomass energy used in Madagascar is still solid charcoal and wood, and the technology is limited. Thus, it is necessary to search for better ways to utilize biomass energy in Madagascar because of high prices of traditional energy carriers and massive environmental pollution. This paper reviews the following: (1) a variety of available biomass wastes for energy in Madagascar including farming residuals, animal wastes, and forest wastes, as well as urban and industrial organic wastes; (2) advanced technologies, such as gasification, torrefaction, and fermentation, that can convert these wastes to biomass energy in forms with higher energy efficiency such as biogas, biocoal briquette, and ethanol fuel, which can not only help to achieve resource utilization of wastes and circular economy but also ease the energy crisis faced by Madagascar; and (3) Madagascar focused on the development of biomass energy with strategic policies and programs. International assistance also contributes to future promotion of biomass energy. It identifies several areas where research is urgently required to adopt instrumental policies to ensure that both rural development objectives and renewable energy targets are met with financial support from the government and international assistance.